2017
DOI: 10.3892/ol.2017.5737
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between intramural pregnancy and choriocarcinoma: A case report

Abstract: Intramural pregnancy is a rare type of ectopic pregnancy with an unclear etiology. It may be associated with uterine wall injury and/or abnormal uterine conditions, such as adenomyosis, in certain cases. In the present report, a case of intramural pregnancy associated with adenomyosis is discussed. The patient was 34 years old and presented with amenorrhea for 40 days. Ultrasonography and magnetic resonance imaging revealed a mixed echogenic mass located within the posterior wall of the uterine fundus with abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…The etiological factors of intramyometrial pregnancy include previous uterine trauma, like hysteromyomectomy [11,13], previous curettage [14][15][16][17], cesarean delivery [6], salpingectomy [18], manual removal of placenta, and especially IVF-ET procedure, resulting in a microscopic sinus tract within the endometrium. Embryo may implant into the myometrium with ectopic endometrial tissues during endometriosis development [19][20][21]. During IVF-embryo transfer, embryo could externally migrate and uterine could perforate due to the active trophoblastic in assisted reproductive treatment [10].…”
Section: Discussionmentioning
confidence: 99%
“…The etiological factors of intramyometrial pregnancy include previous uterine trauma, like hysteromyomectomy [11,13], previous curettage [14][15][16][17], cesarean delivery [6], salpingectomy [18], manual removal of placenta, and especially IVF-ET procedure, resulting in a microscopic sinus tract within the endometrium. Embryo may implant into the myometrium with ectopic endometrial tissues during endometriosis development [19][20][21]. During IVF-embryo transfer, embryo could externally migrate and uterine could perforate due to the active trophoblastic in assisted reproductive treatment [10].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to diagnose an intramural pregnancy can result in catastrophic hemorrhage due to the proximity of the gestational sac to the intramyometrial arcuate vasculature. 9 …”
Section: Discussionmentioning
confidence: 99%
“…The manifestations of intramural ectopic pregnancy such as amenorrhea, lower abdominal pain, and vagal bleeding, are not specific and mimic the symptoms of ectopic pregnancy in other sites (2). These non-specific symptoms can sometimes lead to the misdiagnosis of intramural ectopic pregnancy as myoma, or choriocarcinoma (6). Besides, in previous studies, some patients experiencing intramural ectopic pregnancies reported no discomfort (7), and even the serum β-HCG was negative in one reported case (8).…”
Section: Introductionmentioning
confidence: 89%